2007
DOI: 10.1103/physrevb.75.075304
|View full text |Cite
|
Sign up to set email alerts
|

Damage evolution in low-energy ion implanted silicon

Abstract: The annealing of damage generated by low-energy ion implantation in polycrystalline silicon ͑poly-Si͒ and amorphous silicon ͑a-Si͒ is compared. The rate of heat release between implantation temperature and 350-500°C for Si implanted in both materials and for different ions implanted in poly-Si shows a very similar shape, namely, a featureless signal that is characteristic of a series of processes continuously distributed in terms of activation energy. Nanocalorimetry signals differ only by their amplitude, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Similar thermograms have been measured for other amorphous materials, such as ball milled silicon [3], metallic powders [4] and supercooled alloys [5,6]. The characteristic unstructured signal of structural relaxation is also found in crystalline materials with a high concentration of non-equilibrium point or line defects: cold worked metals [7] and irradiated materials [8]. In these cases the low-temperature transformation is known as recovery.…”
Section: Introductionsupporting
confidence: 56%
“…Similar thermograms have been measured for other amorphous materials, such as ball milled silicon [3], metallic powders [4] and supercooled alloys [5,6]. The characteristic unstructured signal of structural relaxation is also found in crystalline materials with a high concentration of non-equilibrium point or line defects: cold worked metals [7] and irradiated materials [8]. In these cases the low-temperature transformation is known as recovery.…”
Section: Introductionsupporting
confidence: 56%
“…Using ART nouveau [8], a saddle-point finding method, we characterize the evolution of the local energy landscape, defined by the distribution of transition states and adjacent energy minima around a local configuration, as a function of relaxation. The resulting theoretical picture can be used to understand and explain recent nano-calorimetric measurements on ion-implanted a-Si samples [5,6].Our a-Si model is relaxed using the Stillinger-Weber potential with parameters adjusted specifically to recover the structural and vibrational properties of the amorphous system [9]. While this potential has a number of shortcomings, its structural evolution as a function of relaxation is in good qualitative agreement with experiment as discussed below.…”
mentioning
confidence: 78%
“…In spite of these contributions, many questions remain regarding the evolution of the local structure of the energy landscape itself as a function of relaxation, an evolution that determines the dynamics of disordered materials away from equilibrium [5]. For example, following measurements of heat released during the annealing of damage generated by low-energy ion implantation in amorphous silicon, it was suggested that the activation energy and the amount of heat released are uncorrelated [5,6], microscopic details were still missing, however, as well as a general picture of the phenomenon. Results presented here tie experiments and simulations and provide a clear link between the structure of the energy landscape and experimental observations, supporting the importance of this concept.More precisely, we focus on amorphous silicon, a model system studied extensively, both experimentally and theoretically, over the years [4,5,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that damage accumulation reduces the intensity of characteristic peaks [14] and that compressive (tensile) strain shifts phonon modes to higher (lower) frequencies with respect to their bulk values [15,16]. The expected bulk values corresponding to the AlAs and GaAs LO-peaks are 401.5 and 292.1 cm À1 respectively.…”
Section: Raman Spectroscopymentioning
confidence: 93%